Wood utilization in the construction sector : the architects’ perspective - Ab Latib, Hazirah (2016)
The purpose of this study was to analyze the wood utilization in the construction sector in Klang Valley. The specific objective of the study was to identify perception of architects on wood utilization in the construction sector. In addition, the study also aims to determine the choice of wood commonly used and also to determine the factors influencing architects’ for not actively specifying wood for construction purposes in Klang Valley. The study was conducted through the assistance of the Pertubuhan Arkitek Malaysia (PAM) to which survey forms were provided. A total of 25 architects registered in the Klang Valley, volunteered to participate in the study. The study found that there is a general lack of wood use in the construction sector. Most architects who handled projects worth below MYR 1 million did not use wood in their projects. Meanwhile, the architect who handled projects worth more than MYR 1 million used wood as a construction material in their projects. Among the wooden materials widely used in the construction sector are particle board and solid wood such as Kempas (Koompassia malaccensis). There were several factors that contributed to the lack of wood use in the Malaysian construction sector. The lack of supply and its inconsistent quality are the major factors. Based on this study, the construction company did not have a problem with the cost of the wood materials, but the availability affected its use as specified by the architects. Construction companies have to find sufficient supply of wood material, if wood is to be used more widely in the construction sector.